FRI0495 Anti-Ro52 Antibodies Are Strongly Associated with Lung Fibrosis in a Nation-Wide Cohort of Mixed Connective Tissue Disease (MCTD). (10th June 2014) - Gunnarsson, R.; Taraldsrud, E.; El-Hage, F.; Aaløkken, T.M.; Haydon, J.; Garen, T.; Molberg, Ø.
Abstract : Background: MCTD is a disorder characterized by serum auto-antibodies directed against ribonucleoprotein and distinct clinical features including: Raynaud's phenomenon, "puffy hands", arthritis, pleuritis, pericarditis, myositis, esophageal dysmotility, pulmonary hypertension and interstitial lung disease (ILD) (1). Anti-SSA antibodies are directed to two different antigens (Ro52 or Ro60). The Ro52 antigen, a 52 kDa protein, is a part of the tripartite motif protein (TRIM21) family (2). Recent studies have shown that anti-Ro52 antibodies are associated with ILD in systemic sclerosis (3) but were not found to be associated with ILD in a cohort of anti-Jo1-positive patients with antisynthetase syndrome (4). Objectives: To evaluate the association between lung fibrosis and presence of the anti-Ro52 antibody in a well-defined MCTD cohort. Methods: 126 patients, 75% female with a mean disease duration of 9.0 years, were included in the cross-sectional nation-wide unselected Norwegian MCTD cohort, and were examined by high-resolution CT (1). The extent and type of lung abnormalities were scored according to the CT criteria of ILD recommended by the Fleischner Society (5) with reticular patterns consistent with lung fibrosis (1). Serum samples were accessible in 113/126 (90%). The presence of anti-Ro52 and anti-SSB by line immunoassay (ANA Profile 5 Euroline Blot test kit, Euroimmun, Lübeck, Germany). Statistical analyses were performed by SPSS/PASW version 20. Differences between groups were tested by Mantel-Haenszel chi square or Fisher's exact test with two-tailed 95% significance. Results: 57.6% (95%CI; 40.8% to 72.8%) of the MCTD patients with positive anti-Ro52 antibody had lung fibrosis and the risk (odds ratio) was 2.42 higher (95%CI; 1.49 to 3.96) than in those without the antibody. 76.3% (95%CI; 65.8% to 84.3%) of the MCTD patients without the presence of anti-Ro52 did not have lung fibrosis. Conclusions: In MCTD, anti-Ro52 antibodies may be a marker of ILD. As this is a cross-sectional study and the patients could develop ILD in time, the study would probably underestimate the predictive value of positive Ro52 antibody. References: Gunnarsson R et al. Prevalence and severity of interstitial lung disease in mixed connective tissue disease: a nationwide, cross-sectional study. Ann Rheum Dis. 2012;71(12):1966-72. Rhodes DA et al. The 52 000 MW Ro/SS-A autoantigen in Sjogren's syndrome/systemic lupus erythematosus (Ro52) is an interferon-gamma inducible tripartite motif protein associated with membrane proximal structures. Immunology. 2002;106(2):246-56. Hudson M et al. Clinical significance of antibodies to Ro52/TRIM21 in systemic sclerosis. Arthritis Res Ther. 2012;14(2):R50. Marie I, et al. Short-Term and Long-Term Outcome of Anti-Jo1-Positive Patients with Anti-Ro52 Antibody. Semin Arthritis Rheum. 2012;41(6):890-9. Hansell DM et al. Fleischner Society: glossary of terms for thoracic imaging. Radiology. 2008;246(3):697-722. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4660